Immunotherapy with NK cells: recent developments in gene modification open up new avenues. (1st January 2020) - Reindl, Lisa Marie; Albinger, Nawid; Bexte, Tobias; Müller, Stephan; Hartmann, Jessica; Ullrich, Evelyn
ABSTRACT: Chimeric antigen receptor (CAR)-T cell therapies have achieved remarkable success. However, application-related toxicities, such as cytokine release syndrome or neurotoxicity, moved natural killer (NK) cells into focus as novel players in immunotherapy. CAR-NK cells provide an advantageous dual killing-capacity by CAR-dependent and -independent mechanisms and induce few side effects. While the majority of trials still use CAR-T cells, CAR-NK cell trials are on the rise with 19 ongoing studies worldwide. This review illuminates the current state of research and clinical application of CAR-NK cells, as well as future developmental potential.